Kemampuan Prediksi Kepemilikan Manajerial, Biaya Audit, dan Siklus Operasi Terhadap Persistensi Laba - Komalig, Steffani Poppy; Soewignyo, Fanny (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study was conducted to analyze the ability of managerial ownership, audit fees, operating cycle, and firm size as control variable to predict earnings persistence in noncyclical and cyclical companies for the 2019-2021 period.  Using a purposive sampling method, 18 noncyclical companies and 12 cyclical companies were selected. The results showed that in noncyclical companies, managerial ownership, audit fees, and operating cycle could not predict earnings persistence. However, in the cyclical sector, the variation in earnings persistence was determined by managerial ownership, audit fees, and operating cycle by 29.2%. Partially, for the cyclical sector, the results of this study indicate that the higher the managerial ownership, the higher the earnings persistence, indicating that high managerial ownership can minimize agency conflicts and increase earnings persistence. Meanwhile, for audit fees, the higher the amount, the lower the earnings persistence. This result suggests that the more professional the auditor, the less likely the auditor is to compromise financial reports that do not comply with applicable accounting standards. This leads to a tendency for reduced earnings persistence in the audit reports issued. The operating cycle's inability to predict earnings persistence might be due to the operating cycle being more closely related to the company's cash flow, while earnings persistence is related to accrual-based accounting.